Endophytic bacteria: a sustainable strategy for enhancing medicinal plant cultivation and preserving microbial diversity - Semenzato, Giulia; Fani, Renato (Frontiers in Microbiology, 2024)
Endophytic bacteria, part of the plant microbiome, hold significant potential for enhancing the cultivation and sustainability of medicinal plants (MPs). These microbes are integral to many plant functions, including growth promotion, nutrient acquisition, and resistance to biotic and abiotic stresses. However, traditional cultivation practices often overlook the importance of these beneficial microbes, leading to reduced crop yields, lower phytochemical quality, and increased susceptibility to diseases. The domestication of MPs and the use of chemical fertilizers disrupt the natural microbial diversity in soils, essential for the health and productivity of plants. This disruption can lead to the loss of beneficial plant–microbe interactions, which are vital for the production of bioactive compounds with therapeutic properties. Recent advances in microbiome research, supported by omics technologies, have expanded our understanding of how endophytic bacteria can be leveraged to enhance MP productivity and quality. Endophytic bacteria can directly boost MP productivity by promoting plant growth and health or indirectly by restoring healthy soil microbiomes. They can also be harnessed as microbial factories to produce valuable natural compounds, either by transforming plant-derived precursors into bioactive substances or by synthesizing unique metabolites that mimic MP secondary metabolites. This offers a sustainable and low-cost alternative to traditional MP cultivation, reducing the carbon footprint and preserving endangered species. In conclusion, integrating microbiome research with traditional agricultural practices could revolutionize MP cultivation. By focusing on the microbial component, particularly endophytes, we can develop more sustainable and productive methods for cultivating these plants, ultimately contributing to biodiversity conservation and the production of high-value natural products.